Фра Анджелико - Поуп-Хеннесси Джон (Великие мастера итальянского искусства, 1996)
Экземпляры: аб. (1997) / Инвентарный номер: 39474 / Цена: / Сис.шифр: 85.14 / Авт.знак: П 64 / ГРНТИ: 18.31 / ББК: 85.143(4Ита)